THE INFLUENCE OF PRICE PERCEPTION ON GOJEK APPLICATION SERVICE PURCHASE DECISIONS MEDIATED BY EASE OF USE IN MANAGEMENT STUDENTS OF MAKASSAR STATE UNIVERSITY - Ibrahim Syamsuddin; Siti Hasbiah, Muh. Ichwan Musa, Chalid Imran Musa, Ilma Wulansari Hasdiansa (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The research aims to determine the influence of Price Perception on Gojek Application Service Purchase Decisions Mediated by Ease of Use in Management Students of Makassar State University. This study uses a descriptive approach. The population of this study was 1,632. And the sample was active management students of Makassar State University class of 2020-2023 who had used the Gojek application service. The sample was taken using a non-probability sampling method with a judgmental sampling approach and using the slovin formula to determine the sample so that a minimum sample of 94 respondents was obtained. Data were collected through questionnaires and analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) Version 3.00 application.The results of the study indicate that (1) Price Perception (X) has a direct, positive and significant effect on the Purchase Decision of Gojek Application Services, (2) Price Perception (X) has an indirect, positive and significant effect on the Purchase Decision Mediated by the Ease of Use of Gojek Application Services on Management Students of Makassar State University.